Flexible Metal–Air Batteries: Progress, Challenges, and Perspectives. Issue 2 (27th November 2017) - Liu, Qingchao; Chang, Zhiwen; Li, Zhongjun; Zhang, Xinbo
Abstract: Flexible metal–air batteries, which are a promising candidate for implantation in wearable or rolling‐up electronic devices, have attracted much attention recently due to their relatively high energy density. Various flexible metal–air batteries have been developed recently, including flexible nonaqueous lithium–air batteries, aqueous zinc–air batteries, and aqueous aluminum–air batteries. Although various viable configurations of flexible metal–air batteries have been proposed, challenges regarding electrode design, electrolyte exploitation, and low practical energy density, still exist. Here, a brief introduction is presented as to the recent development of flexible metal–air batteries, regarding the electrodes, electrolyte, and prototype devices. Also, a general perspective on the current challenges and recommended future research directions for the practical use of metal–air batteries is provided. Abstract : Flexible metal–air batteries are identified as one of the most promising candidates for use in flexible energy‐storage devices, such as portable and wearable electronics. The development of the flexible electrode design, electrolyte exploitation, and the assembly of prototype batteries are comprehensively reviewed. The major challenges and perspectives for flexible metal–air batteries are also discussed.